Effect of Glutamine, Biotin and ADP on Micropropagation and Growth of Chrysanthemum hybridum, Gerbera jamesonii and Cordyline fruticosa In vitro (Plant Tissue Culture and Biotechnology, 2016)
The effect of glutamine, biotin and adenosine diphosphate (ADP) on growth and cultivars micropropagation of three ornamental species was investigated. The addition of 10 ? 100 mg/l glutamine in culture media significantly increased rate of multiplication in Cordyline fruticosa and 100 mg/l glutamine showed the same effect for Gerbera jamesonii. Addition of glutamine did not show any effect on shoot length, root number and length in all the three species. Addition of 1 ? 3 mg/l biotin increased shoot length of Gerbera jamesonii but inhibited shoot length of Cordyline fruticosa and decreased root length of Chrysanthemum hybridum and Gerbera jamesonii. Addition of 5.0 mg/l ADP significantly increased multiplication rate of Cordyline fruticosa and 1.0 mg/l ADP showed similar effect for Gerbera jamesonii.Plant Tissue Cult. & Biotech. 26(1): 97-104, 2016 (June)